THE ROLE OF PARENTING STYLE AND ENVIRONMENT IN SHAPING WORKPLACE MINDSET: A STUDY IN CENTRAL JAVA - Adam Sasando; Primadia Putri Harmastuti (PT Akselerasi Karya Mandiri, 2025)
This study aims to analyze the influence of parenting style and environment on workplace mindset. Workplace mindset is a mindset that influences how individuals respond to challenges, work in teams, and adapt to organizational dynamics. This study uses a quantitative approach with the Partial Least Square (PLS 3.0) analysis method, involving 100 respondents from various regions in Central Java. The results showed that parenting style and environment significantly influenced workplace mindset, with an R-square value of 0.505, which means that both variables are able to explain 50.5% of the variation in individual work mindsets. These findings indicate that childhood experiences through parenting style and the influence of the social environment such as relationships and lifestyle have an important role in shaping a person's professional attitudes and ways of thinking. Therefore, the development of a positive work mindset needs to consider psychosocial aspects from an early age. Practically, organizations and educational institutions are encouraged to integrate character-building programs that emphasize emotional intelligence and adaptive thinking from a young age to support long-term professional development.